Analysis of spatial patterns of oak decline in cork oak woodlands in Mediterranean conditions - Costa, Augusta; Pereira, Helena; Madeira, Manuel (Annals of Forest Science, 2010)
• Cork oak mortality is a recurrent problem in southwestern Portugal. Despite the perception of increasingly visible damage in oak woodlands on drought-prone sites, the role of the various environmental factors in their decline is not clear. • To describe the spatial patterns of cork oak (Quercus suber L.) mortality, a cork oak mortality index (MI) was determined for each landscape feature (agroforestry system, soil type, slope and aspect) using a GIS approach. To achieve this goal, a logistic regression model was formulated analyzing interactions between landscape attributes and allowing a prediction of cork oak mortality. • Maximum values of MI were found in (i) shrublands and open woodlands with shrub encroachment (MI 6 and 3, respectively), where competition for soil water between tree and understory increases; and (ii) on lower slopes in the rounded hilltops and smooth hillsides or shallow soils where access to groundwater resources during summer drought is diﬃcult. • The model highlighted the importance of the agroforestry systems on cork oak mortality and may be used to identify sensitive areas where mitigation actions should be employed in a scenario of increasing drought severity in these Mediterranean ecosystems.
Keywords: Logistic regression; Oak decline; oak mortality; Quercus suber L.; Remote sensing